2010
DOI: 10.1111/j.1469-7580.2010.01266.x
|View full text |Cite
|
Sign up to set email alerts
|

Building a human cortex: the evolutionary differentiation of Cajal‐Retzius cells and the cortical hem

Abstract: Cajal-Retzius (CR) cells are the most significant source of reelin, an extracellular matrix glycoprotein essential for cortical development. Strategically located in the marginal zone, CR cells control radial migration and laminar positioning of pyramidal neurons of the cortical plate. They degenerate and undergo cell death when cortical migration is completed. In human cortex development, reelin-expressing CR cells are already present in the early preplate, and continue to increase in number after the appeara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
103
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(105 citation statements)
references
References 61 publications
2
103
0
Order By: Relevance
“…As already mentioned, the first generated neurons, C-R and SP cells are located respectively in the presumptive Layer 1 and the SP zone of the human cortical anlage [66,98,99]. Specific to human, the SP zone is the largest transient compartment of the fetal neocortical anlage, about four times thicker than the cortical plate around midgestation [66,100].…”
Section: Specificities Of the Human And Primate Cerebral Cortexmentioning
confidence: 86%
“…As already mentioned, the first generated neurons, C-R and SP cells are located respectively in the presumptive Layer 1 and the SP zone of the human cortical anlage [66,98,99]. Specific to human, the SP zone is the largest transient compartment of the fetal neocortical anlage, about four times thicker than the cortical plate around midgestation [66,100].…”
Section: Specificities Of the Human And Primate Cerebral Cortexmentioning
confidence: 86%
“…Gundela Meyer has shown that the earliest cortical structure, the preplate, has a more complex structure in humans than in rodents (Meyer, 2007(Meyer, , 2010 in this issue) (Fig. 3B,C).…”
Section: Human-specific Aspects Of the Earliest Stages Of Cortical Dementioning
confidence: 87%
“…12 th to 14 th week: S100-positive astrocytes appear in the fimbria and hippocampus (Janas et al 1991), the subpial granular layer (SGL), containing CRCs, is formed (Gadisseaux et al 1992;Meyer 2010) and the outer subventricular zone (OSVZ) can be distinguished . 15 th to 21 st week: CRCs and SGL cells descend to a deeper position within the marginal zone (MZ) (Meyer 2010). The superficial part of the subpial glial end feet layer has not yet transformed into a subpial glia limitans, which occurs at 25 th to 28 th wpc (Kadhim et al 1988).…”
mentioning
confidence: 99%
“…9 th to 11 th week: The intermediate zone (IZ) and subplate (SP) can be separated by different markers (Bystron et al 2008) and microglia appear in the telencephalon (Rezaie et al 2005). 12 th to 14 th week: S100-positive astrocytes appear in the fimbria and hippocampus (Janas et al 1991), the subpial granular layer (SGL), containing CRCs, is formed (Gadisseaux et al 1992;Meyer 2010) and the outer subventricular zone (OSVZ) can be distinguished . 15 th to 21 st week: CRCs and SGL cells descend to a deeper position within the marginal zone (MZ) (Meyer 2010).…”
mentioning
confidence: 99%